An Efficient Multipath Packet Forwarding (MPF) Protocol with Modified Dijkstra Path Searching Algorithm in Underwater Wireless Sensor Network - Devi, P; Ramesh, T (International Journal of Computer Sciences and Engineering, 2020)
Underwater Wireless Sensor network is an emerging to be a promising technology in unveiling the mysteries of the marine life and other underwater applications. Routing in underwater wireless sensor networks differs from routing in global wireless sensor networks. However, distinctive features of UWSNs like multipath propagation delay, limited bandwidth, and energy constraints. This paper presents a Multipath Packet Forwarding (MPF) protocol with modified Dijkstra path searching algorithm is used for dynamic data transmission in this work. The proposed Multipath Packet Forwarding protocol is used for multiple paths which loops free and disjoint in message communication. In addition, during the path selection of the best shortest path forwarder node, the robust weight function parameters make it more efficient to consume minimum energy. The experimental result analysis indicates that Multipath Packet Forwarding (MPF) protocol with modified Dijkstra path searching algorithm has very good adaption ability to the UWSN in terms of Throughput, Packet Delivery Ratio (PDR), Packet Loss Ratio and Energy consumption.